KINERJA PEGAWAI DINAS KEHUTANAN KABUPATEN INDRAGIRI HILIR - Eko Budi Santoso; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to explain how the performance of employees in the Indragiri Hilir District Forest Service. Assessment of Civil Servants is carried out based on Government Regulation Number 10 of 1979 concerning Evaluation of the Implementation of Civil Servants' Work. In this study the author uses employee performance theory. To bridge the theory of the performance of employees of the Indragiri Hilir District Forestry Service the author uses a frame of mind referring to the views of Mathis and Jackson called the Elements of Employee Performance. In his view the performance performance theory will consider the aspects of quantity, quality, timeliness, presence and ability to cooperate. The results of this study, the quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. The Indragiri Hilir District Forestry Service must be clear in the division of labor and workload that is evenly distributed across various fields so that it focuses on work in accordance with its responsibilities, providing opportunities for employees to attend training specifically in accordance with their duties and tasks carried out periodically. Keywords: Performance, Employees, Forest Service of Indragiri Hilir Regency